Pengaruh Sikap Wajib Pajak terhadap Kepatuhan Wajib Pajak dalam Pembayaran Pajak Bumi dan Bangunan di Kabupaten Magetan - Muryati, Ninik; Wibisono, Haris; Mujilan, Agustinus (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2016)
This study aims to discover the influence of the attitude of tax payer toward tax payer compliance in Magetan. The result of this study can give the benefit and input for relevant agencies and other researchers. The population of this study were the PBB tax payer which registered on the Register of Tax Assessment Association Magetan 2013. Sum of the sample were 105 respondents which distribute in 18 districts. The quality test of data using validity and reliability test. Data analysis technique using classical assumption (normality test, autocorrelation, multicollinearity test, heteroscedasticity test), test hypotheses (t test and F test). This study found evidence that the attitude of tax payer towards regional development priority, the attitude of tax payer on the implementation of PBB fines, the attitude of tax payer towards fiscus service have significant effects on the tax payer compliance in Magetan. However, the attitude of tax payer that the evasion on the PBB has been common has no effect on the tax payer compliance in Magetan.